China-Pakistan Economic Corridor: Socio-Cultural and Political Implications for Pakistan Amid Covid19 and the Way Forward - Dr. Mubeen Adnan; Reema Murad (Journal of Political Studies, 2023)
Through the ‘game changer’ project of China Pakistan Economic Corridor, China is aiming to stabilize its western part by promoting investment and economic development in its neighbour to the West, Pakistan, which will lead to a boost in the Pakistani economy through investments in infrastructure and construction of gas and oil pipeline. There is also the aim of reducing extremism in the Xinjiang region. However, there are several social, cultural and political changes that the project has the potential to bring about in Pakistan. This research work has made an attempt to understand the variousimplications of the China Pakistan Economic Corridor on Pakistan as well as how the COVID-19 pandemic impacted CPEC and the path ahead as the world slowly transitions out of COVID-19. This research paper has used secondary sources in order to answer these pertinent topics. Major opportunities which Pakistan and China have gained through this ChinaPakistan economic Corridor as well as some challenges are also discussed.